Evaluasi Kepuasan Mahasiswa Terhadap Layanan Bimbingan Akademik di Program Studi Sarjana Kebidanan - Feri Anita Wijayanti; Hindun Mila Hudzaifah; Yulizawati; Ulfa Farrah Lisa (Cetta: Jurnal Ilmu Pendidikan, 2023)
The quality of academic services can affect students' satisfaction at the university. The aim of this study was to evaluate students' satisfaction with the academic services provided by lecturers in the bachelor of midwifery study program. A descriptive design was utilized in this study. The population was active Bachelor of Midwifery students, Faculty of Medicine, Andalas University, in 2022, using a sample of 191 respondents with purposive sampling. Indicators of students' satisfaction with academic services included reliability, responsiveness, assurance, empathy, and tangibles. Data was collected using a ten-item questionnaire developed by the researchers with a Likert scale (1-4). This study was conducted in October 2022 using an online form. The respondents' level of achievement was in the fairly satisfactory category. The empathy indicator had the highest average TCR value among other indicators and was within the satisfied category. This research may give insight into providing opportunities for faculty management, especially study programs, to overcome weaknesses in the offered services and ensure better academic service quality. In addition, this research will stimulate more research attention on how the quality of academic services by academic supervisors can give better satisfaction to students.